Arduino-based real-time data acquisition systems: boosting STEM career interest - Prabowo, Norbertus Krisnu; Paristiowati, Maria; Irwanto, Irwanto (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study examines the development of an Arduino-based real-time data acquisition system and its effect on secondary students’ STEM career interest (STEM-CIS). A total of 74 students were sampled from a prestigious private school in Jakarta, Indonesia, and a learning device was developed using the A.D.D.I.E. method. A one-group pretest-posttest research design was used to evaluate the effect of using the device during blended classroom activities. Data were collected through surveys using the STEM-CIS instrument and interviews. The study was based on the general practice of using Arduino software and hardware for practical purposes in Chemistry Laboratories and Sick Bay. The setup was successfully used in these different environments as a temperature monitoring system to record thermochemistry data and monitor a patient’s body temperature. The findings are consistent with prior research indicating that hands-on robotics activities can increase STEM interest and inspire students to pursue STEM careers. The results suggest that strong engagement in this activity facilitated the development of digital literacy and STEM skills. The STEM-CIS score at the 5% significance level was significantly increased after the experimentation with the device, with a paired t-test result of p<0.001. The effect size (Cohen’s d) showed a moderate effect of 0.74.